(3QSGdI GdENhGf ef Cgd Gdabg hMedI GdbQBfs - (3Ydj Hf ejehf Hf CHj HcQ Hf jhSa GdgGTej GdMSfj GdEOQjSj GdaGSj GdeZQHj, GHf ejehf , CHh GdMSf,J (B917 (3g` s ((3YHO GdhgGH Hf SdjeGf Hf YHO GdhgGH GdghT s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO ajbhd Ydi Hf ejehf hQO Ydi ai ChGNQ GdYTQ GdChd ef LeGO GdChd SfI NeS YTQI hJSYeGFI Cf CcJH QSGdI Ydi ebJVi Sdhc GdWQjb GdeMeOi s
(3BNQgG (B:s
(3bO ef Gddg HJeGe JbjjO eG hbYJ Edjg GdETGQI ai GdUOQ hCSCdg HESMGfg Cf jLYdg Hg dg hCf jfaY Hg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B741s
Keywords: (3GdJUha hGdBOGH GdTQYjIs